hrWaC and slWac: compiling web corpora for Croatian and Slovene - Ljubešić, Nikola, informatičar; Erjavec, Tomaž (2011)
Web corpora have become an attractive source of linguistic content, yet are for many languages still not available. This paper introduces two new annotated web corpora: the Croatian hrWaC and the Slovene slWaC. Both were built using a modified standard “Web as Corpus” pipeline having in mind the limited amount of available web data. The modifications are described in the paper, focusing on the content extraction from HTML pages, which combines high precision of extracted language content with a decent recall. The paper also investigates text-types of the acquired corpora using topic modeling, comparing the two corpora among themselves and with ukWaC.
Projekt MZOS
ENG